Turkey's Double Standard Policy Towards Israel During the Presidency of Recep Tayyip Erdogan from 2019 to 2021 - Pratama, M Rizki (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research is entitled Turkey's Double Standard Politics Against Israel in the Era of President Recep Tayyip Erdogan's Government in 2019-2021. This study was conducted to find out the efforts made by the Turkish government in responding to its foreign relations with Israel based on its country's national interests. This study uses descriptive qualitative methods and the primary data in this study is Ms. Dina Sulaeman, she is a lecturer in International Relations at Padjadjaran University and is an expert or expert on matters relating to political and policy coverage in the Middle East region. While the secondary data in this study are books, international journals, archives or reports of someone who is related to the research. The data analysis technique used qualitative analysis techniques, namely data reduction, data presentation, and drawing conclusions/verification. The results of this research indicate that the double standard politics carried out by the Turkish government against Israel is a representation of Turkey's national interests. Every Turkish foreign policy towards Israel, both positive and negative policies always refers to Turkey's national interests where foreign policy always prioritizes the principle of balance between security and democracy, zero problem policy toward Turkey's neighbors, developing relations with neighboring countries, implementing multidimensional foreign policy, and rhythmic diplomacy